Inhibitory Activity of Andrographolide and Andrograpanin on the Rate of PGH2 Formation - Sumiwi, Sri A.; Halimah, Eli; Saptarini, Nyi M.; Levita, Jutti; Nawawi, Asari; Mutalib, Abdul; Ibrahim, Slamet (Pharmacology and Clinical Pharmacy Research)
Cyclooxygenase (COX) or prostaglandin H2 synthase (PGHS) catalyzes the conversion of arachidonic acid into prostaglandins. Nonsteroidal anti-inflammatory drugs (NSAIDs) work by inhibiting both COX-1 and COX-2 isoforms, thus disturbing this reaction. In Indonesia, Andrographis paniculata (local name: sambiloto), is empirically used to reduce inflammation by consuming the herb tea of this plant. This work studied the inhibitory activity of andrographolide and andrograpanin, diterpenoids of the plant, on the rate of prostaglandin formation. Previous works have proven that andrographolide inhibited PGE2 production in LPS-induced human fibroblast cells. This study was performed by measuring the absorbance of TMPD (tetramethyl-p-phenyldiamine) oxidized by andrographolide and andrograpanin. Acetosal was used as a control drug. The rate of PGH2 formations on either COX-1 or COX- 2 was affected by andrographolide and andrograpanin. Andrographolide and andrograpanin interact longer with COX-1 than COX-2. Andrographolide shows weak inhibition on the rate of PGH2 formation, whilst andrograpanin might be further developed for potential antiinflammatory drugs.Keywords: Andrographis paniculata, anti-inflammatory, COX, cyclooxygenase, prostaglandin